2015
DOI: 10.1186/s13014-015-0364-1
|View full text |Cite
|
Sign up to set email alerts
|

Integration of BOLD-fMRI and DTI into radiation treatment planning for high-grade gliomas located near the primary motor cortexes and corticospinal tracts

Abstract: BackgroundThe main objective of this study was to evaluate the efficacy of integrating the blood oxygen level dependent functional magnetic resonance imaging (BOLD-fMRI) and diffusion tensor imaging (DTI) data into radiation treatment planning for high-grade gliomas located near the primary motor cortexes (PMCs) and corticospinal tracts (CSTs).MethodsA total of 20 patients with high-grade gliomas adjacent to PMCs and CSTs between 2012 and 2014 were recruited. The bilateral PMCs and CSTs were located in the nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 21 publications
2
35
1
Order By: Relevance
“…Whether the integration of fMRI information into RT treatment planning could further improve patients’ prognosis is an interesting and open research question. It has already been shown feasible by Wang et al [ 41 ] who reported no significant difference between the 3DCRT and IMRT plans in terms of dose homogeneity while in the same time maximizing the dose to the tumor and sparing functional regions. However, it is still premature to draw a final conclusion on the factors leading to alterations in the connectivity as many factors play a role.…”
Section: Discussionmentioning
confidence: 97%
“…Whether the integration of fMRI information into RT treatment planning could further improve patients’ prognosis is an interesting and open research question. It has already been shown feasible by Wang et al [ 41 ] who reported no significant difference between the 3DCRT and IMRT plans in terms of dose homogeneity while in the same time maximizing the dose to the tumor and sparing functional regions. However, it is still premature to draw a final conclusion on the factors leading to alterations in the connectivity as many factors play a role.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, previous research investigating incorporating functional information into RT plans has relied extensively on task-based fMRI acquisition [2][3][4][5][6][7]. These previous studies have predominately focused on avoiding damage to functional relevant networks that are associated with sensory processing or language production.…”
Section: Main Findingsmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) presents the ability to selectively protect functionally significant regions of the brain during radiation therapy (RT) of primary brain tumors [1]. Previous investigations have focused on incorporating task-based fMRI information from sensory networks (motor, visual, auditory) or language networks into conventional treatment plans [2][3][4][5][6][7]. In addition, multiple investigators have demonstrated the feasibility of incorporating tissue-specific functional information derived from advanced imaging modalities into treatment plans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A planning study has shown that integrating diffusion tensor tractography into IMRT planning has significantly reduced radiotherapy dose to the corticospinal tract in patients with glioblastoma (91). In another study of 20 patients with high-grade glioma, bilateral motor cortex and corticospinal tracts were marked using integrated DTI and BOLD-fMRI as organs at risk (OARs), which led to a reduction in the dose of radiotherapy using IMRT (92). Thus studies have shown that both DTI and BOLD-fMRI can be integrated into planning CT/MRI scan to delineate critical nerve tracks and eloquent regions for functional avoidance radiotherapy (figure 2).…”
Section: The Potential For Integrating Modern Imaging With Novel Radimentioning
confidence: 99%